2006
DOI: 10.1007/s11010-006-9324-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell proliferation and induction of apoptosis by genistein in experimental hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the leading cause of cancer related deaths in the world, with increasing incidence in many developed countries. Epidemiological data suggest that consumption of soy products may be associated with a decreased risk of cancer. We investigate the effects of genistein on cell proliferation, apoptosis and caspase-3 in DEN induced (200 mg/kg body weight; by single intraperitoneal injection) and Phenobarbital promoted (0.05% through drinking water for 14 successive weeks) cancer-bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…We also found that genistein induced cell cycle progression arrest at the G0/G1 and G2/M phases. These data are in accordance with other reports which showed that genistein induced cell cycle progression arrest at the G2/ M phase and that the number of S phase cells decreased in a progressive way as the genistein incubation time was increased [15,19,20] . Although the exact mechanisms of action of genistein have yet to be fully elucidated, induction of apoptosis may be partly responsible.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that genistein induced cell cycle progression arrest at the G0/G1 and G2/M phases. These data are in accordance with other reports which showed that genistein induced cell cycle progression arrest at the G2/ M phase and that the number of S phase cells decreased in a progressive way as the genistein incubation time was increased [15,19,20] . Although the exact mechanisms of action of genistein have yet to be fully elucidated, induction of apoptosis may be partly responsible.…”
Section: Discussionsupporting
confidence: 93%
“…Because PCNA has been used as a proliferation index to reflect tumor growth because of its high levels in proliferating cells (55,(73)(74)(75), reduction of PCNA stability or acceleration of PCNA degradation might offer an effective strategy for regulating tumor growth. UV irradiation is a universal DNA-damaging factor, which acts mainly by inducing formation of DNA photoproducts between adjacent pyrimidine bases on the same strand such as cyclobutane pyrimidine dimers (CPDs) and (6 -4) photoproducts (6 -4PPs) (76).…”
Section: X-x-(a)-(a)]mentioning
confidence: 99%
“…129 In fact, studies have found that genistein inhibits the growth of various cancer cell lines as a result of inhibition of protein tyrosine kinase activity. [137][138][139] The mechanism of these antiproliferative effects appears to be mediated through genistein's ability to inhibit NFB activation by the Akt or Notch-1 signaling axis. 139,140 However, genistein has also been shown to induce apoptosis through additional factors such as caspase-3 activation (an end-effector of apoptosis) and reduction in mitochondrial membrane potential.…”
Section: Phytoestrogensmentioning
confidence: 99%